Flow cytometric applicability to evaluate UV inactivation of phytoplankton in marine water samples. Issue 1 (15th July 2015) - Olsen, Ranveig Ottoey; Hess-Erga, Ole-Kristian; Larsen, Aud; Thuestad, Gunnar; Tobiesen, August; Hoell, Ingunn Alne
Highlights: We use flow cytometry (FCM) to evaluate UV irradiation on phytoplankton. A FCM protocol was developed that clearly separates live and dead T. suecica . Cfu was used to develop gates in FCM dot plots for live T. suecica cells. The FCM protocol can be used to analyze UV based water treatment applications. Abstract: Disinfection of microbes is of importance to prevent the spread of pathogens and non-indigenous species in the environment. Here we test the applicability of using flow cytometry (FCM) to evaluate inactivation of the phytoplankter Tetraselmis suecica after UV irradiation and labeling with the esterase substrate 5-carboxyfluorescein diacetate acetoxymethyl ester (CFDA-AM). Non-irradiated and UV irradiated samples were analyzed with the plate count technique and FCM for 24 days. The numbers of colony forming units were used as a standard to develop a FCM protocol. Our protocol readily distinguishes live and dead cells, but challenges were encountered when determining whether UV damaged cells are dying or repairable. As damaged cells can represent a risk to aquatic organisms and/or humans, this was taken into account when developing the FCM protocol. In spite of the above mentioned challenges we argue that FCM represents an accurate and rapid method to analyze T. suecica samples.